A constituição do sujeito na adolescência e a escrita de si: escolhas profissionais e produção de sentidos - Freitas, Francine Rocha de (2020)
The current work approaches the thematic of professional choice in the context of adolescence. It is registered at Cabinet of Projects (GAP), No. 048944, reviewed and approved by the Committee of Ethics in Research (CEP) of Federal University of Santa Maria (UFSM) on July 11, 2018, Caae registered No. 92770318.2.0000.5346. Since the adolescent subject fills a space in between childhood and adulthood, where they find themselves and are socially acclaimed to make a professional choice, our objective is to comprehend, from the theoretical-methodological assumptions of the pecheuxtian Speech Analysis, the adolescent subject gestures of interpretation are accomplished with the need for professional choice, from the self-writing as a tool that allow the subject to discursive the matter demanded for them. Regarding the methodology applied to compose the file, we performed the data collect by field study, being the analysis and interpretation device established from the French line Speech Analysis, proposed by Michel Pêcheux and his pairs in France, as well as it has been developed in Brazil by Eni Orlandi and others. There were participating 33 subjects members of five 3rd grade classes, regularly enrolled in five State High Schools of the central region of Rio Grande do Sul, during the period between August and September, 2018. There were selected 45 discursive sequences belonging to 30 dissertation activities of self-writing in order to constitute a corpus that allow us to analyze the linguistic-discursive marks of/on the speech of these subjects. As final considerations, from a file reading gesture, we comprehend that it is possible to note, in the relation between the subjects and their professional choice, a movement among “what is happiness” “and” / “or” “what brings money”, as well as between “to be” “and” / “or” “to do”, and we observe the operation of the modalities of subjectivation proposed by Pêcheux ([1975] 1995) as the identification and counter-identification relatives to the behavior of social formation and, especially, four Discursive Formations, which we nominate as Familiar and Scholar (described from the “Ideology and Ideological State Apparatuses”, from Althusser [1985]), and Adolescent and Economical (which we comprehend as global)”.